The Attractive Banality of Natalia LL’s "Consumer Art” (1972–1975) - Jakubowska, Agata (Nordlit, 2007)
The article is an analysis of the reception of "Consumer Art" by Natalia LL. The work is a series of photographs and films made in the years 1972-1975 featuring women consuming bananas, sausages, custard and starch jelly.The work was created in the neo-avant-garde circles and was in those circles perceived as "an exploration of morphological potential of the sign and the capacity of the medium" (Andrzej Lachowicz). Simultaneously it functioned in the sphere of feminist art, into which it was included in the 1970's by feminist researchers from the Western Europe. In the present article the author conducts an analysis of the ambivalence resulting from the inclusion, which is caused by, among other factors, the incompatibility of Western discourse to Polish situation. It is also pointed out that it is only in the second half of the 1990's that the feminist discourse re-appears in the declarations of the artist herself and of some critics, which is related to the shift, observable in their texts, of "Consumer Art" from the area of conceptual art to the area of body art. The author enters a polemic with some elements of those interpretations, e. g. those referring to the critique of consumerism, and proposes to concentrate on the work by Natalia LL as one referring to erotic desire and female pleasure as issues which had no proper place in the mainstream culture (in the case of Natalia LL, the culture of the Polish Republic of Poland). In this context the author recalls the contemporary pastiche of Natalia LL's work, "Try this!" (2006) by Karol Radziszewski.
Keywords: Natalia LL; neo-avant-garde; feminist art; conceptual art; consumerism; Karol Radziszewski; pleasure